2011
DOI: 10.1002/chem.201101899
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Cleavage of an Aromatic CC Bond by Tungsten

Abstract: The pathway for the cleavage of an aromatic C-C bond in quinoxaline by a tungsten(II) complex [W(PMe(3))(4)(η(2)-CH(2)PMe(2))H] is explored by performing detailed DFT calculations. The real active complex was found to be [W(PMe(3))(2)(η(2)-CH(2)PMe(2))H] rather than [W(PMe(3))(4)]. The key step in the whole reaction is the reductive elimination of two hydrides that are located originally on quinoxaline (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This CÀCi nsertion is the rate determining step with the overall barriero f3 2.6 kcal mol À1 .H owever,s uch activation energy is quite high for the observed reaction conditions (90 8C, 24 h). Av ariation of this mechanism was reported by Yoshizawa et al [27] with much lower barrier of 17.2 kcal mol À1 correspondingt or eductive eliminationo fd ihydrogen. In ac ompeting paper,Z hang et al proposed an alternative mechanismthat involves aC ÀHactivation, rate-determining insertion into the ring CÀCb ond, second CÀHa ctivation and elimination of dihydrogen.…”
Section: Metal Insertion Into Arene Ring With Prior Chemical Modificamentioning
confidence: 58%
See 1 more Smart Citation
“…This CÀCi nsertion is the rate determining step with the overall barriero f3 2.6 kcal mol À1 .H owever,s uch activation energy is quite high for the observed reaction conditions (90 8C, 24 h). Av ariation of this mechanism was reported by Yoshizawa et al [27] with much lower barrier of 17.2 kcal mol À1 correspondingt or eductive eliminationo fd ihydrogen. In ac ompeting paper,Z hang et al proposed an alternative mechanismthat involves aC ÀHactivation, rate-determining insertion into the ring CÀCb ond, second CÀHa ctivation and elimination of dihydrogen.…”
Section: Metal Insertion Into Arene Ring With Prior Chemical Modificamentioning
confidence: 58%
“…However, such activation energy is quite high for the observed reaction conditions (90 °C, 24 h). A variation of this mechanism was reported by Yoshizawa et al . with much lower barrier of 17.2 kcal mol −1 corresponding to reductive elimination of dihydrogen.…”
Section: Metal Mediated C−c Scission In Arenes and Heteroarenesmentioning
confidence: 99%
“…The good agreement between the two sets of energies confirms that B3LYP/(6-31G(d)+ LANL2DZ) provides an appropriate balance of accuracy and performance to allow detailed enumeration of multiple reaction paths in multiple Cp*Ir( narene) complexes, which distinguishes our current work from computational studies of arene C-C bond scission in the literature. 20,21,[23][24][25] We computed enthalpies and free energies by adding the thermodynamic corrections to the single-point energies calculated at the M06-L/(6-311+G(d)+LANL2TZ) level with a conductor polarizable continuum model (CPCM) of the reaction solvent. Our calculations led to one lowest energy (dominant) mechanism that involves reversible benzylic C-H activation, and three higher energy mechanisms that occur via (a) aromatic C-H activation, (b) double benzylic and aromatic C-H activation and (c) without C-H activation.…”
Section: Dft Calculations Of the Reaction Mechanismsmentioning
confidence: 99%
“…The reported mechanistic studies of observed arene C-C cleavage are limited to benzene 16,[20][21][22] or quinoxaline [23][24][25] and are exclusively computational. These DFT calculations focused primarily on C-C scission following reduction or dehydrogenation of the aromatic ring 20,21,[23][24][25] instead of the more fundamentally and synthetically important but little-understood C-C scission in intact arenes. 14,22,26 Two known computationally identified examples of direct aromatic C-C activation in substituted arenes have never been realized experimentally, illustrating the challenges of integrating experimental and computational approaches in this area.…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that the W‐based reaction is initiated by the direct W‐bonded hydrogen migration of the substrate without dissociation of one PMe 3 ligand. Very recently, Li and Yoshizawa18 presented another molecular mechanism study of this reaction, in which the reductive elimination of two hydrides that are originally located on QoxH is believed to be the key step of the entire reaction. To further elucidate the mechanism of this important and novel type of reaction and to understand how the tungsten complex activates the aromatic CC bond, we performed extensive density functional theory (DFT) calculations, from which we expected to answer 1) what the detailed mechanism of the unusual CC activation is; 2) whether Sattler and Parkin’s mechanism is available for understanding the observed cleavage of the aromatic CC bond; and 3) if not, what the feasible pathway should be.…”
Section: Introductionmentioning
confidence: 99%